Correlation of Bullying Behavior with Students' Social Interaction Attitudes at MTSs Mu'allimin Muhammadiyah Pakan Sinayan - Hafifah Rahmawati; Aulia Fitrianti; Nurul Hasanah (KIPS Institute, 2025)
Bullying behavior has recently become very common, especially in educational institutions, and this certainly has an impact on children's social interactions. The purpose of this study was to determine whether there is a relationship between bullying behavior and the social interaction attitudes of students at MTsS Mu'allimin Muhammadiyah Pakan Sinayan. The approach uses a quantitative method with a correlational research type. The population is 221 people and the sample is 54 people obtained through the proportional sample technique. The results of the calculation of the number of variable X scores and variable Y scores are entered into the product moment correlation formula to connect the two scores, which are consulted in the r product moment table at a confidence level of 0.05. r-count is greater than r-table (0.028> 0.268). The results of the study indicate that there is a positive relationship between bullying behavior (variable X) and students' social interaction attitudes (variable Y).